Travelers’ responses to online information on consumer-generated media for travel-related services - Kusumasondjaja, Sony (Curtin University, 2012)
This research is aimed to investigate how travel consumers respond to online information posted in Consumer-Generated Media. It was examined the impact of consumer characteristics (risk propensity and Internet experience), information characteristics (information valence and information quality), and source characteristics (source identity and similarity) on consumer perception of information credibility, trust in the travel services being discussed, and intention to purchase the services. Hypotheses and research questions were proposed based on the concept of uncertainty reduction and information processing. A 3x2 between-subject experimental research design was developed. Information valence and source identity were manipulated. The survey was conducted at several popular tourist destinations in Bali involving 1939 real travel consumers holidaying in Bali as participants.Results show significant effects of risk propensity, information quality, and similarity on perception of information credibility, trust in travel services being reviewed, and intentions to purchase the services. Internet experience was found not significant in affecting credibility, trust, and purchase intention. The study also confirmed the main and interaction effects of information valence and source identity on perception of information credibility, trust in travel services being reviewed, and intentions to purchase the services. Information with identified source was perceived to be more credible and leads to greater trust and consumer purchase intention than unidentified information. Balanced information was found to have greatest impact on credibility, trust, and intention. Positive information was suggested to have the least impact on credibility, as well as negative information on trust and purchase intention. The interaction of balanced information with identified source was found to have the greatest influence on credibility, trust, and intention, while negative information with unidentified source was found to have the least effect. Several conceptual, methodological, and research contributions offered by this study are also discussed.